Strain mediated enzymatic degradation of arterial tissue: Insights into the role of the non-collagenous tissue matrix and collagen crimp. (1st September 2018) - Gaul, R.T.; Nolan, D.R.; Ristori, T.; Bouten, C.V.C.; Loerakker, S.; Lally, C.
Graphical abstract: Abstract: Collagen fibre remodelling is a strain dependent process which is stimulated by the degradation of existing collagen. To date, literature has focussed on strain dependent degradation of pure collagen or structurally simple collagenous tissues, often overlooking degradation within more complex, heterogenous soft tissues. The aim of this study is to identify, for the first time, the strain dependent degradation behaviour and mechanical factors influencing collagen degradation in arterial tissue using a combined experimental and numerical approach. To achieve this, structural analysis was carried out using small angle light scattering to determine the fibre level response due to strain induced degradation. Next, strain dependent degradation rates were determined from stress relaxation experiments in the presence of crude and purified collagenase to determine the tissue level degradation response. Finally, a 1D theoretical model was developed, incorporating matrix stiffness and a gradient of collagen fibre crimp to decouple the mechanism behind strain dependent arterial degradation. SALS structural analysis identified a strain mediated degradation response in arterial tissue at the fibre level not dissimilar to that found in literature for pure collagen. Interestingly, two distinctly different strain mediated degradation responses were identified experimentally at the tissue level, not seen in other collagenous tissues. Our model was able to accurately predict these experimental findings, but only once the load bearing matrix, its degradation response and the gradient of collagen fibre crimp across the arterial wall were incorporated. These findings highlight the critical role that the various tissue constituents play in the degradation response of arterial tissue. Statement of Significance: Collagen fibre architecture is the dominant load bearing component of arterial tissue. Remodelling of this architecture is a strain dependent process stimulated by the degradation of existing collagen. Despite this, degradation of arterial tissue and in particular, arterial collagen, is not fully understood or studied. In the current study, we identified for the first time, the strain dependent degradation response of arterial tissue, which has not been observed in other collagenous tissues in literature. We hypothesised that this unique degradation response was due to the complex structure observed in arterial tissue. Based on this hypothesis, we developed a novel numerical model capable of explaining this unique degradation response which may provide critical insights into disease development and aid in the design of interventional medical devices.